Developing a ubiquitous health management system with healthy diet control for metabolic syndrome healthcare in Taiwan. (June 2017) - Kan, Yao-Chiang; Chen, Kai-Hong; Lin, Hsueh-Chun
Highlights: This study establishes a prototype of ubiquitous healthcare management system with healthy diet control (UHMS-HDC). UHMS-HDC provides the diet diary function with personalized health criteria to help people controlling diet habits. The system constructs three multi-disciplinary portals on Web-based and mobile-enabled interfaces with a database tier. The site "WebHealthControl" in UHMS-HDC processes online health information and management for iHealth and eHealth. The mobile application "HealthControlApp" in UHMS-HDC can write the diet diary for m-Health. The diet and nutrition database (DNDB) and personal health database (PHDB) in UHMS-HDC store the healthcare information. The personalized dietary guideline can be created in UHMS-HDC for the users to assess their health risk. The online diagrams and analytical modules in UHMS-HDC support medical care feedback for self-health management. The self-developed system can be promoted for metabolic syndrome healthcare and is expandable for more chronic diseases. Abstract: Background and Objective: Self-management in healthcare can allow patients managing their health data anytime and everywhere for prevention of chronic diseases. This study established a prototype of ubiquitous health management system (UHMS) with healthy diet control (HDC) for people who need services of metabolic syndrome healthcare in Taiwan. Methods: System infrastructure comprises of three portals and a database tier with mutually supportive components to achieve functionality of diet diaries, nutrition guides, and health risk assessments for self-health management. With the diet, nutrition, and personal health database, the design enables the analytical diagrams on the interactive interface to support a mobile application for diet diary, a Web-based platform for health management, and the modules of research and development for medical care. For database integrity, dietary data can be stored at offline mode prior to transformation between mobile device and server site at online mode. Results: The UHMS-HDC was developed by open source technology for ubiquitous health management with personalized dietary criteria. The system integrates mobile, internet, and electronic healthcare services with the diet diary functions to manage healthy diet behaviors of users. The virtual patients were involved to simulate the self-health management procedure. The assessment functions were approved by capturing the screen snapshots in the procedure. The proposed system development was capable for practical intervention. Conclusion: This approach details the expandable framework with collaborative components regarding the self-developed UHMS-HDC. The multi-disciplinary applications for self-health management can support the healthcare professionals to reduce medical resources and improve healthcare effects for the patient who requires monitoring personal health condition with diet control. The proposed system can be practiced for intervention in the hospital.